A dynamic model for predicting the falling number of rye grains in Finnish (Ostrobothnian) conditions - Laurila, Leena; Karvonen, Tuomo; Hiivola, Sirkka-Liisa (Agricultural and Food Science, 1992)
This study was carried out with two primary goals in mind. Firstly, the purpose was to study the behaviour of the falling number of rye during the growing season in South Ostrobothnia. Secondly, the aim was to study the effect of air temperature and precipitation on the falling number and to develop a mathematical model for predicting the daily changes in the falling number of rye. Falling number data was collected at the Research Station of South Ostrobothnia of the Agricultural Research Centre in 1975-1987. The varieties used in the study were Anna, Hankkija’s Jussi, Sampo, Toivo and Voima. On the basis of the falling number measurements and the daily weather data, a dynamic model for predicting the daily changes in falling number of rye was designed. The most important independent variables of the model are maximum air temperature and precipitation. The dynamic model predicted most accurately the falling number of the variety Anna. The coefficient of determination was 0.81. The lowest coefficient of determination was 0.70 for the varieties Sampo and Toivo. The maximum falling number was high in the years with warm periods during the maturing of the kernel. The threshold was 23 °C. In these years the dynamic model was not capable of predicting the highest falling number. Moreover, the predicted decrease in the falling number was usually faster than the measured one. The low falling numbers in South Ostrobothnia were mostly not due to low maximum falling number but to the fact that the maximum was reached early at the milk ripening stage, and at that moment rye was too moist to be harvested. After the maximum was reached, the falling number started to decrease due to precipitation and/or temperature.